Examining the Visitors’ Experiences While Visiting Sri Baduga Museum - Sri Mulyanah; Pradipta Dirgantara; Naufal Ardiyanto (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2025)
Understanding the visitors’ experiences when they visit a museum might provide better information to the museums’ researchers and curators the strategies to improve the services given by a museum. One of the museums in Indonesia that aims to improve their service is Sri Baduga Museum. Located in Bandung, West Java, Sri Baduga Museum has an extensive collection of Sundanese cultural artifacts such as traditional fabrics, traditional farming tools, traditional games, traditional musical instruments, antique sculptures, and  ancient Sundanese manuscripts. Hence, the objective of this study is to investigate the experiences of a group of visitors of Sri Baduga Museum. We used a qualitative research design by conducting in-depth interviews to eight participants. The results of this study show that most participants think Sri Baduga Museum has provided them with a set of diverse collections that give them educational experiences while visiting the museum. In addition to raising awareness toward the culture of Sundanese, the participants think Sri Baduga Museum is able to show them how ancient Sundanese survived by living harmoniously with nature, giving them new perspectives to live in the modern era. The implications of this study suggest the necessity to improve the quality of a museum to help the next generation understand their own culture and educate more people.